Geological Setting of the NERCO Con Mine and the Relationship of Gold Mineralization to Metamorphism, Yellowknife, N.W. T. - D. W. McDonald; N. A. Duke; R. L. Hauser (Canadian Institute of Mining, Metallurgy and Petroleum, 1993)
"Abstract- The NERCO Con Mine is situated in the amphibolite facies aureole of the Western Plutonic Complex overprinting the Yellowknife Greenstone Belt. Metamorphic grade of the upright monoclinal basaltic succession decreases from hornblende-amphibolite facies along the border of the batholith to greenschist facies. Metamorphic isograds, subparalleling the faulted margin of the batholith, transect volcanic stratigraphy and coincide with major gold bearing shears.Gold mineralization is confined to north-striking, west-dipping shear zones where hanging wall amphibolite facies mineral assemblages retrogress to chlorite-carbonate-sericite-sulfide bearing schists hosting multiple generations of quartz-ankerite veins. The gold-producing portions of the Con and Campbell Shears occur where these structures transect an east trending thermal corridor. The corridor is defined by granitic plugs and a number of related breccia bodies, that can be traced outwards from the batholith across the greenstone belt.Prograde reactions of greenstone during amphibolitization effectively liberate fluids that partition metals. With retrograde reactions at shear zones, gold is precipitated with quartz due to the destabilization of sulfide and arsenic complexes. The coupling of regional prograde metamorphic and restricted retrograde metasomatic overprints suggest mineralization is temporally related to emplacement of the Western Plutonic Complex. Economic gold concentrations within the intrusive corridor indicates enhanced metamorphic overprint of hornfelsed greenstones enveloping satellite intru sives peripheral to the main batholith."